Do Direct Cash Flow Disclosures Help Predict Future Operating Cash Flows and Earnings? - Orpurt, Steven F. (Institutional Knowledge at Singapore Management University, 2009)
Motivated by recent FASB, IASB, and CFA Institute comments, we explore the predictive value of direct method cash flow disclosures. A primary stated purpose of the direct method is to better forecast future performance. To examine this purpose, we first document that direct method line items, such as cash received from customers, are not reliably estimable using income statements and either balance sheets or indirect method statements of cash flows. When these estimation (articulation) errors are included in cash flows and earnings forecasting models, forecasting performance significantly improves. In addition, employing a future ERC (FERC) methodology, we find evidence suggesting that market participants utilize direct method disclosures for their stated purpose: to better forecast future operating performance. After conducting several tests for self-selection concerns, we conclude that the direct method is valuable to investors when forecasting future cash flows and earnings.